Unconscious affective processing and empathy: an investigation of subliminal priming on the detection of painful facial expressions - Yamada, Makiko; Decety, Jean (Pain (Amsterdam), 2009)
Results from recent functional neuroimaging studies suggest that facial expressions of pain trigger empathic mimicry responses in the observer, in the sense of an activation in the pain matrix. However, pain itself also signals a potential threat in the environment and urges individuals to escape or avoid its source. This evolutionarily primitive aspect of pain processing, i.e., avoidance from the threat value of pain, seems to conflict with the emergence of empathic concern, i.e., a motivation to approach toward the other. The present study explored whether the affective values of targets influence the detection of pain at the unconscious level. We found that the detection of pain was facilitated by unconscious negative affective processing rather than by positive affective processing. This suggests that detection of pain is primarily influenced by its inherent threat value, and that empathy and empathic concern may not rely on a simple reflexive resonance as generally thought. The results of this study provide a deeper understanding of how fundamental the unconscious detection of pain is to the processes involved in the experience of empathy and sympathy.